APLIKASI ANGGARAN PADA PERUM PERHUTANI DIVISI REGIONAL JAWATIMUR - Widowati, Widowati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the application of budget at Public Company Indonesian State Forestry Enterprise East Java Regional Divison. Budgeting is the financial planning of an organization or the preparation process of written plan about the activity of an organization which is stated quantitatively and is generally stated in units of money, whereas budget is the number of money which is planned for an activity in a certain period. The effectiyeness according to Blocher Chen and Gary cokins is the operation in its goal has been determined from the operation. Efficient means not to waste resources in carrying out its operation in vain. An operation will be inefficient if the company does not use its resources over their target. The result of the research that has been obtained in accordance with Departement of Interior No. 690.900.327 of 1996 the total of activity cost which is used by Perum Perhutani Divisi Regional Jawa Timur is Rp. 26.450.000 from the total of activity cost plan is Rp. 26.000.000 with the ratio 98% of the budget has been used effectively yet in is inefficient whereas, according to Blocher Chen and Gary cokins the total cost from production statement which has been used is Rp. 26.450.000 from the RKAP Rp. 26.000.000 or 99.8% of the budget has been used effectively. The volume of realization is 204.456 M2 whereas the RKAP that has been determined by management is 195.254 M2 has been effectively used.Keywords: budgeting, effective, efficiency, Production Statement